Multicenter prospective study to optimize the efficacy of triple therapy with telaprevir in patients with genotype 1b hepatitis C virus infection according to an algorithm based on the drug Adherence, IL‐28B Gene Allele and Viral Response Trial (AG & RGT). Issue 11 (3rd March 2015) - Sugawara, Kayoko; Koushima, Youhei; Inao, Mie; Nakayama, Nobuaki; Nagoshi, Sumiko; Yakabi, Koji; Tamano, Masaya; Asabe, Shinichi; Nishikawa, Ko; Harada, Youji; Sekine, Chuichi; Fukuya, Yuji; et al.
Abstract : Aim: To optimize the therapeutic efficacy of NS3/4A protease inhibitors, a multicenter prospective study was performed according to an algorithm based on the Adherence, IL‐28B Gene Allele and Viral Response Trial (AG & RGT). Methods: A total of 340 patients with genotype 1b hepatitis C virus (HCV) showing serum RNA levels of >5 log were enrolled. The duration of ribavirin/pegylated interferon (PEG IFN)‐α‐2b therapy was prolonged to 48 weeks in patients with unfavorable IL28B alleles showing adherence rates of less than 80% for either drug during the first 12 weeks even if RVR had been achieved, and in those in whom cEVR, but not RVR, was achieved; furthermore, to 72 weeks in those showing partial early viral response. Results: The therapeutic outcomes were assessed in 282 patients, and the therapy was set to complete at 24 weeks in 181 patients (64%) and to prolong to 48 weeks or 72 weeks in 71 patients (25%). The former group showed a SVR rate of 84%, while the latter group showed an SVR rate of 69% with a relapse rate of 7%. The SVR rate was 33% in the 30 patients (11%) in whom the therapy had to be discontinued in less than 12 weeks. Thus, the results of intention‐to‐treat analysis revealed an overall SVR rate of 75%. Multivariate analysis identified prolongation of the duration of therapy as a significant factor associated with SVR. Conclusion: Triple therapy yielded a high SVR rate in the AG & RGT trial via attenuation of viral relapse by prolonged ribavirin/PEG IFN‐α‐2b administration. © 2015 The Japan Society of Hepatology